Isolation and characterization of Staphylococcus aureus from bovine clinical mastitis - Kumar, C.N Naveen; Prakash, B; Muniyappa, L; Krishnappa, G; Moorthy, A.R.S (The Indian Journal of Animal Sciences, 2007)
Staphylococcus aureus isolates (9) were isolated from 40 clinical cases of bovine mastitis and were subjected to antibiogram and protein profile analysis. Antibiogram studies revealed that most of the isolates were sensitive to ciprofloxacin, cephalexin, enrofloxacin, erythromycin and amoxycillin but were resistant to ampicill/cloxacillin, streptomycin, penicillin, neomycin and furazolidone. Based on the protein profile analysis the Staph. aureus isolates were classified into three strains; the SA1 strain which was resistant to most of the antibiotics was found to be a variant strain compared to other isolates.